The Effect Of Self-Efficacy And Organizational Commitment On The Employee Performance Of The Courier Division At PT. Jalur Nugraha Ekakurir (JNE) Main Branch Jember (Jurnal Strategi dan Bisnis, 2022)
Abstract This study aims to determine and analyze: (1) The Effect of Self-efficacy on Performance; (2) Effect of Organizational Commitment on Performance; (3) Simultaneous Effect of Self-efficacy and Organizational Commitment on Performance. This type of research is an associative research with a quantitative approach using multiple linear regression analysis, where this research was conducted at PT. Jalur Nugraha Ekakurir (JNE) Main Branch of Jember. The independent variables in this study are Self-efficacy (X1) and Organizational Commitment (X2), while the dependent variable is Performance (Y). All existing research variables are measured using a Likert scale that has been modified into 4 options. The sample used in the study amounted to 50 respondents namely employees of the courier division at PT. Jalur Nugraha Ekakurir (JNE) Main Branch of Jember. The type of data in this study are primary and secondary data. Testing instruments using the validity and reliability test. Based on the results of this study it can be concluded that self-efficacy and organizational commitment have a significant positive effect on the performance of the courier division employees at PT. Jalur Nugraha Ekakurir (JNE) Main Branch of Jember, both partially and simultaneously. Keywords: Self-efficacy, Organizational Commitment, Performance